Hindu Nation and its Queers: Caste, Islamophobia, and De/coloniality in India - Upadhyay, Nishant (Interventions (London, England), 2020)
The 2018 Indian Supreme Court judgement decriminalizing homosexuality has been marked as a "decolonial act." Section 377, which criminalized homosexuality, was a colonial law introduced by the British in India, which the postcolonial state maintained till 2018. The judgement may be "decolonial" in intent, but there are other simultaneous processes at play which are not so decolonial in praxis; this essay argues these processes are colonialism, brahminical supremacy, and Islamophobia. Caste-based violence is integral to Hinduism and intertwined with other matrices of oppression, making caste foundational to any claims of Hinduism as queer, trans and gender nonconforming friendly. Studying recent Hindu nationalist responses in favour of decriminalization of homosexuality in India, this essay traces how the Hindu Right deploys queerness to propagate its Islamophobic, casteist, and homohindunationalist agendas. The essay argues decolonizing the law, state, and sexuality would also mean annihilating caste and brahminical structures.